On the $L_p -L_q$- estimates for the solutions of certain hyperbolic equations - Markovskii, A. I.; Марковский, А. И.; Марковский, А. И. (Institute of Mathematics, NAS of Ukraine, 1993)
We establish conditions, which should be imposed on the exponentsp andq and the dimensionalityn of a space in order that the $L_p -L_q$-estimates should hold for the solutions of the Cauchy problem for a second-order hyperbolic equation with constant coefficients.